Natural disease course of Crohn's disease during the first 5 years after diagnosis in a European population-based inception cohort: an Epi-IBD study. Issue 3 (23rd January 2018) - Burisch, Johan; Kiudelis, Gediminas; Kupcinskas, Limas; Kievit, Hendrika Adriana Linda; Andersen, Karina Winther; Andersen, Vibeke; Salupere, Riina; Pedersen, Natalia; Kjeldsen, Jens; D'Incà, Renata; Valpiani, Daniela; Schwartz, Doron; et al.
Abstract : Objective: The Epi-IBD cohort is a prospective population-based inception cohort of unselected patients with inflammatory bowel disease from 29 European centres covering a background population of almost 10 million people. The aim of this study was to assess the 5-year outcome and disease course of patients with Crohn's disease (CD). Design: Patients were followed up prospectively from the time of diagnosis, including collection of their clinical data, demographics, disease activity, medical therapy, surgery, cancers and deaths. Associations between outcomes and multiple covariates were analysed by Cox regression analysis. Results: In total, 488 patients were included in the study. During follow-up, 107 (22%) patients received surgery, while 176 (36%) patients were hospitalised because of CD. A total of 49 (14%) patients diagnosed with non-stricturing, non-penetrating disease progressed to either stricturing and/or penetrating disease. These rates did not differ between patients from Western and Eastern Europe. However, significant geographic differences were noted regarding treatment: more patients in Western Europe received biological therapy (33%) and immunomodulators (66%) than did those in Eastern Europe (14% and 54%, respectively, P<0.01), while more Eastern European patients received 5-aminosalicylates (90% vs 56%, P<0.05). Treatment with immunomodulators reduced the risk of surgery (HR: 0.4, 95% CI 0.2 to 0.6) and hospitalisation (HR: 0.3, 95% CI 0.2 to 0.5). Conclusion: Despite patients being treated early and frequently with immunomodulators and biological therapy in Western Europe, 5-year outcomes including surgery and phenotype progression in this cohort were comparable across Western and Eastern Europe. Differences in treatment strategies between Western and Eastern European centres did not affect the disease course. Treatment with immunomodulators reduced the risk of surgery and hospitalisation.